E-Commerce Platforms as Business Agility Reinforcement To Compete In The Market: Cases Of Indonesian MSME - Tisyani, Aisha Salsabila; Sushandoyo, Dedy (Journal Integration of Management Studies, 2023)
Despite having many vulnerabilities for being small, around 99.99% of businesses in Indonesia belong to the MSME category. Many companies consider going digital to face vulnerabilities such as limited resources, fierce competition, and environmental changes. Among all the different approaches to Digital Transformation, adopting a digital business ecosystem like an e-commerce platform is more suitable for MSMEs for its source and cost efficiency. However, only around 19% of the total number of MSMEs in Indonesia have adopted a digital business ecosystem by using e-commerce platforms. This study explores the impacts e-commerce platforms brought to various business aspects in MSMEs and whether e-commerce adoption help reinforce MSMEs' business agility to remain competitive in the market. To reach the aim of the study, we used qualitative research by interviewing six small business owners utilizing e-commerce platforms. The findings of this study show that adopting an e-commerce platform has generated changes that positively impact four business aspects: business operation, organization, marketing, and product development. These changes signify an improvement in agility. By gaining this knowledge, we hoped this study could serve as a guide to motivate more MSMEs to venture into the digital realm through e-commerce platforms.